Toxicity of g-csf given during radiotherapy in lung cancer - Nawrocki, Sergiusz; Karczmarczyk, Agnieszka; Cieślak, Ewa (Contemporary Oncology/Współczesna Onkologia, 2006)
Introduction: The use of white blood cell growth factors (WBCGF) (g-csf, gm-csf) is recommended in chemotherapy-induced febrile neutropenia or prophylactically for cases treated with some chemotherapy regimens. Due to lack of sufficient data the use of WBCGF is not recommended in patients receiving radiotherapy and concomitant chemotherapy. There are reports showing that the use of WBCGF at the time of chemo-radiotherapy can lead to thrombocytopenia, particularly when radiotherapy involved chest tumours, the mechanism of which remains unclear. In the curative treatment of limited- -disease small cell lung cancer (LD SCLC) and also in non-small cell lung cancer (NSCLC) delays and prolongation of the treatment time, especially in combined modality therapy, may worsen clinical outcomes. Purpose: Evaluation of the safety of the administration of G-CSF with the concomitant chemoradiation for lung cancer, particularly the incidence of severe thrombocytopenia and its complications. Methods: From lung cancer patients treated with curative intent between January 2004 and June 2006 in the Radiotherapy Department in Olsztyn 27 patients (25 LD SCLC, 2 NSCLC) received chemo-radiotherapy with the G-CSF given during radiotherapy course. G-CSF was administrated for 3-10 days (average 6 days). 10 patients received G-CSF twice during the radiotherapy course. Toxicity was assessed during and after the treatment. Results: Grade 3-4 thrombocytopenia (according to Common Toxicity Criteria – CTC) occurred in 13 patients. Platelets were administrated to 2 patients. 1 patient had haemoptysis probably associated with thrombocytopenia. No other serious side effects were observed. Conclusions: The use of G-CSF during curative chemoradiation for lung cancer to avoid treatment interruptions seems to be safe, especially regarding thrombocytopenia and its complications. Due to limitations related to small sample size and no control group, a prospective randomized study with the administration of G-CSF during radiation compared with administration during radiation therapy breaks is justified.